2015
DOI: 10.1146/annurev-orgpsych-032414-111322
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype Threat in Organizations: Implications for Equity and Performance

Abstract: Over the past 20 years, a large body of laboratory and field research has shown that, when people perform in settings in which their group is negatively stereotyped, they may experience a phenomenon called stereotype threat that can undermine motivation and trust and cause underperformance. This review describes that research and places it into an organizational context. First, we describe the processes by which stereotype threat can impair outcomes among people in the workplace. Next, we delineate the situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 176 publications
1
91
0
Order By: Relevance
“…Therefore, diversity obligations are recognized by members of both minority and majority identity groups. However, employees from historically disadvantaged social groups are more vigilant about monitoring diversity signals and more sensitive to cues about whether organizations value their social identity (Walton, Murphy, & Ryan, 2015). Therefore, they are less likely to perceive their organization as meeting its diversity management obligations, thus reporting lower diversity promise fulfillment (Buttner, Lowe, & Billings-Harris, 2010b;Chrobot-Mason, 2003).…”
Section: The Problem Of Employee Commitmentmentioning
confidence: 99%
“…Therefore, diversity obligations are recognized by members of both minority and majority identity groups. However, employees from historically disadvantaged social groups are more vigilant about monitoring diversity signals and more sensitive to cues about whether organizations value their social identity (Walton, Murphy, & Ryan, 2015). Therefore, they are less likely to perceive their organization as meeting its diversity management obligations, thus reporting lower diversity promise fulfillment (Buttner, Lowe, & Billings-Harris, 2010b;Chrobot-Mason, 2003).…”
Section: The Problem Of Employee Commitmentmentioning
confidence: 99%
“…Gunter and Stambach (2005) characterize university science departments as masculine cultures based on the interpersonal interactions typical of masculine norms, situated in a setting that promotes a "detached" "rational" approach to knowledge. Women entering historically male-dominated STEM fields face persistent stereotypes that foster marginalization and may trigger fears of negative social comparison due to gender (Good et al 2012;Kiefer and Sekaquaptewa 2007;Logel et al 2009;Smyth and Nosek 2015;Walton et al 2015). For female students, university STEM programs are particularly "gendered organizations" given the high proportion of males in high-ranking positions (Britton et al 2012;Fox et al 2011;White and Ivie 2013), especially at the graduate level where the proportion of female students and faculty drops (White and Ivie 2013).…”
Section: The Gendered Culture Of Stem Graduate Educationmentioning
confidence: 99%
“…Research has consistently demonstrated that during evaluation processes, managers and workers are vulnerable to multiple biases-including racial differences (e.g., Arvey & Murphy, 1998;Emerson & Murphy, 2014;Ford, 1986;Sackett & DuBois, 1991;Walton, Murphy, & Ryan, 2015). Studies have shown that African-American workers receive lower performance scores compared with White workers on both subjective and objective measures, especially when the evaluators are White (Arvey & Murphy, 1998;Knight, Hebl, Foster, & Mannix, 2003).…”
Section: Work Contact-reducing Prejudice and Negative Attitudesmentioning
confidence: 99%